(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2021)
The purpose of this essay is to investigate the role played by regional film agencies in the new Millenium production of TV crime drama in the UK by looking in particular at the portfolio of Screen Yorkshire. The recent development of production hubs and the global competition for studio spaces, location, and facilities, led to increased importance of regional settings and support for the screen industries which is evident in the activities of national and regional agencies in the UK. After an overview of the location market in the UK and the production support available at the regional level, the essay will address the crime narratives set in local settings, and the role played by the film agencies, in particular Screen Yorkshire. Screen Yorkshire since its establishment in 2002 proved successful in developing the growth of screen industries in the area, thanks to its specialisation in commercial content investment and the introduction of the Yorkshire Content Fund (YCF). The essay will engage with the different supporting mechanisms available in the areas, through the analysis of the crime productions to reveal how matters of location and heritage play a role in the crime narratives.